2013
DOI: 10.1007/s40262-013-0038-9
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamic, Pharmacokinetic and Pharmacogenetic Aspects of Drugs Used in the Treatment of Alzheimer’s Disease

Abstract: With the aging population and its rapidly increasing prevalence, dementia has become an important public health concern in developed and developing countries. To date, the pharmacological treatment is symptomatic and based on the observed neurotransmitter disturbances. The four most commonly used drugs are donepezil, galantamine, rivastigmine and memantine. Donepezil, galantamine and rivastigmine are acetylcholinesterase inhibitors with different pharmacodynamic and pharmacokinetic profiles. Donepezil inhibits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
123
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(128 citation statements)
references
References 124 publications
2
123
0
3
Order By: Relevance
“…In the EU, the maximum recommended dose is 10 mg daily, and in the USA the FDAapproved dose is 23 mg daily (Doody et al 2008;Farlow et al 2010;Noetzli and Eap 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the EU, the maximum recommended dose is 10 mg daily, and in the USA the FDAapproved dose is 23 mg daily (Doody et al 2008;Farlow et al 2010;Noetzli and Eap 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Donepezil is well absorbed, with a bioavailability approaching 100 %. Peak plasma concentrations (Cmax) are achieved after 3-5 h in patients receiving immediaterelease (5-and 10-mg tablets) and 6 h in those receiving sustained-release (23-mg tablet) formulations (see Table 1; taken from Noetzli and Eap 2013). In the USA, the FDAapproved dose is higher at 23 mg daily.…”
Section: Introductionmentioning
confidence: 99%
“…Drug therapy for patients with impaired cognitive and/or excretion is applied. 31) It is reported that patients receiving high doses of donepezil, a medication for Alzheimer's disease, developed urinary dis- 32,33) The involvement of pharmacists in the drug therapy of such patients would be beneficial and provide a better care environment for the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Учитывая предполагаемое влияние ИХЭС на амилои-догенез и прогрессирование дегенеративного процесса, ре-комендуется раннее начало терапии. Эффективность лече-ния напрямую зависит от дозы препарата и продолжитель-ности терапии, что в свою очередь непосредственно связано с наличием побочных эффектов и переносимости [48]. Для преодоления нежелательных явлений используют посте-пенное повышение дозы, малый шаг титрации дозы, разра-батывают безопасные лекарственные формы и новые спо-собы введения.…”
unclassified
“…Кли-нические данные об эффективности Акатинола меманти-на ® показывают улучшение или сохранение (на более поздних стадиях) когнитивных и психомоторных функ-ций, обучаемости, повседневной деятельности, снижение зависимости от опекунов [49,50]. На метаболизм препа-рата не влияет система цитохрома Р450, поэтому вероят-ность возникновения лекарственных взаимодействий до-статочно низкая [48]. Эффективность мемантина зависит от дозы.…”
unclassified